Cash pooling as a state-of-the-art cash management method in the capital group - Poskart, Robert (Cash pooling jako nowoczesna usługa zarządzania środkami pieniężnymi w grupie kapitałowej, 2011)
Companies in the capital group, due to the large amount of cash flows between related parties, some of which show a surplus and other financial shortages, use modern financial services in order to optimize the financial results of the group Cash pooling is one of these services
Nauki o Finansach = Financial Sciences, 2011, Nr 1 (6), s. 148-156
Keywords: virtual cash pooling; real cash pooling; optimization of financial flows; capital group